Scanning electron microscopy of dermatofibroma - Felipe Simões Lopes Quintana; Hiram Larangeira de Almeida Jr; Caroline Pires Ruas; Valéria Magalhães Jorge (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Dermatofibroma is a proliferation of spindle cells located in the dermis. We used scanning electron microscopy to examine two histologically confirmed lesions and observed preserved collagen bundles in the perilesional area. In the lesional area, the collagen was denser, without formation of bundles. Higher magnification showed collagen with mesh-like appearance similar to stretched tufts of cotton. Very high magnification evidenced the tufts of cotton and spindle cells measuring 2 to 12 microns.